Determinação voltamétrica de zinco empregando eletrodos quimicamente modificados com bismuto - Fonseca, Wilson Tiago da (2016)
This dissertation presents the development of voltammetric methods to zinc determination in multivitamin commercial samples, talc, and art materials for painting (soft pastel) combining an alkaline extraction with 1.0 mol L-1 NaOH aqueous solution and bismuth modified electrodes. Two electrodes were used to zinc quantification in the samples, bismuth film electrode (BiFE) plated in situ onto glassy carbon and carbon paste electrode chemically modified with strongly acidic ion exchange resin Amberlite® IR 120 and bismuth nanostructures (EPCAmbBi). It was verified that the best concentration of Bi3+ for Bi film deposition onto glassy carbon was 4.0 μmol L-1 using an 0.1 mol L-1 acetate buffer aqueous solution (pH = 4.5) as supporting electrolyte. The best condition to formation of Bi nanostructures in the EPC modified with 10 % Amberlite® IR 120 was the use of 30 s to pre-concentration (open circuit) in 0.5 mmol L-1 Bi3+ aqueous solution (pH 5.5) prepared with supporting electrolyte solution. The obtained analytical curve for Zn2+ using BiFE presented linear range from 0.5 to 5.0 μmol L-1, the limit of detection (LD) was 41 nmol L-1. For EPCAmbBi only one linear range was observed for the analytical curve varying the Zn2+ concentration from 0.05 to 8.2 μmol L-1, LD obtained in this curve it was equal to 10 nmol L-1. The EPCAmbBi presented the most intense and sharp anodic stripping peaks for Zn2+ presenting, therefore, a better voltammetric profile, with sensitivity higher than obtained with the BiFE. Moreover, the EPCAmbBi presented a LD lower than that obtained with the BiFE. Alkaline extraction was an efficient sample pretreatment to extract Zn2+ from solid samples, besides that, this procedure was less susceptible to interferences from Cu2+, since it remains at extracting vessel as insoluble Cu(OH)2. The combination of alkaline extraction with the EPCAmbBi is a simple, fast, efficient and low cost for the zinc determination in pharmaceutical formulations and art materials for painting (soft pastel) samples, which can be employed as a low-cost alternative method to the atomic absorption spectroscopy.